2015
DOI: 10.1186/s12913-015-0922-0
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of the barriers and facilitators of HIV counselling and testing perceived by adolescents in South Africa

Abstract: BackgroundYouth in South Africa have been identified as a high-risk group for contracting HIV. In response, the South African Integrated School Health Policy (ISHP) has been developed with the aim of guiding the provision of comprehensive healthcare services within South African schools. Accordingly, the scale-up of HIV counselling and testing (HCT) in high schools is a priority. This study examines the factors affecting the utilisation of HCT services amongst learners in high schools in the KwaZulu-Natal prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
61
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 32 publications
11
61
1
Order By: Relevance
“…This study highlights that, by gathering main consensual elements that integrate the AIDS SR -a frightening disease that causes suffering and fear when one thinks about HIV contamination, and is associated with socially reproachable behaviors (sex and drugs) -it is possible to understand the reasons that support the stereotype that forms the AIDS stigma, which consequently reproduces and stresses prejudices that favor marginalization and its social consequences (7,(24)(25) .…”
Section: Discussionmentioning
confidence: 94%
“…This study highlights that, by gathering main consensual elements that integrate the AIDS SR -a frightening disease that causes suffering and fear when one thinks about HIV contamination, and is associated with socially reproachable behaviors (sex and drugs) -it is possible to understand the reasons that support the stereotype that forms the AIDS stigma, which consequently reproduces and stresses prejudices that favor marginalization and its social consequences (7,(24)(25) .…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, qualitative studies establishing the barriers to testing for this age group should be encouraged. Those barriers are likely to be specific to both the testing strategy and the setting [20, 44]. …”
Section: Discussionmentioning
confidence: 99%
“…Our research uniquely identified participants' self‐convincing process as they initiated the decision to seek testing. The participants who identified this prompt were relatively younger and may experience mental testing barriers like stigma and fear that remain deterrents of HIV testing (Phillips, Ybarra, Prescott, Parsons, & Mustanski, 2015; Schnall et al, 2015; Strauss, Rhodes, & George, 2015). Hence, the ability to assuage feelings of concern with the knowledge of HIV testing benefits through self‐convincing was essential for young adults to initiate testing decisions.…”
Section: Discussionmentioning
confidence: 99%